(untitled) (Journal of NELTA, 2011)
In many English language learning and teaching contexts the absence of literary texts, such as graded readers, short stories and poems, still seems to be the norm. This article looks briefly at the some more recent historical positions regarding the use of literature in ELT, and then discusses how the inclusion of creative reading material may foster the development of reading and critical thinking skills. Key words: Literature; Language input; Poetic language; Web 2.0 Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 110-113 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4616